Pergeseran dari Offshoring ke Friend-Shoring: Penataan Ulang Strategis Rantai Nilai Global dalam Menghadapi Fragmentasi Geopolitik Dunia - Aldi Adi Pratama (Universitas Tridinanti, 2025)
The world is currently witnessing a fundamental transformation in the global economic architecture, marked by a shift from the paradigm of offshoring driven by extreme cost efficiency toward